2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--18540
|View full text |Cite
|
Sign up to set email alerts
|

The Engagement and Retention of Electrical Engineering Students with a First Semester Freshman Experience Course

Abstract: Tyler, where he develops curriculum and laboratories in computer engineering. Prior to this he worked at Texas Instruments specializing in real time imaging systems. Dr. Shirvaikar graduated with his doctorate from the University of Tennessee. He also has a M.S. degree from the University of Maine, and a B.Tech. from Banaras Hindu University, India. His current research interests include real time imaging and engineering education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As described in Section 3, real-world examples are given at different times in class according to the material covered, which maintains students' interests in EE or EET fields, as other studies suggested [1,[4][5][6]. Because the method also helps all students keep up with the course material, it prevents some students from dropping the class or program early because of their lower performance in the first core course in EE or EET programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in Section 3, real-world examples are given at different times in class according to the material covered, which maintains students' interests in EE or EET fields, as other studies suggested [1,[4][5][6]. Because the method also helps all students keep up with the course material, it prevents some students from dropping the class or program early because of their lower performance in the first core course in EE or EET programs.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons according to student surveys from different groups at different campuses in both two-year associate programs and four-year programs the author worked with. The gap between basic theories in textbooks and the real applications in our modern life and work, especially in the EET field, makes some students feel that they learn a great deal of useless material rather than real technology, which they expected to learn in college when they selected the program [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Department of Electrical Engineering at UT Tyler is one of the oldest departments in the College of Engineering, which offers Bachelor of Science in Electrical Engineering (BSEE) and Master of Electrical Engineering (MSEE) at both the Tyler and Houston campuses. Though the College of Engineering was primarily an upper-division school, offering the continuing education curriculum for transfer students from community colleges, the freshmen and sophomore enrollment had started in Fall 1998 [14]. As an ABET-accredited BSEE program, the curriculum focuses on providing more hands-on experience for undergraduates at all levels.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…There are benefits of having portable hands-on learning equipment. Among the benefits are improved student engagement [6,7,8], and improved student learning [9]. In addition, the usage of portable equipment allows the hands-on activities to be adaptable to traditional lecture courses [4,10,11], lab settings [5], and homework/project activities [4].…”
Section: Introductionmentioning
confidence: 99%